Flood - Vachss, Andrew H (London William Collins Sons & Co. Ltd., 1986)
Burke's newest client is a woman named Flood, who has the face of an angel, the body of a high-priced stripper, and the skills of a professional executioner. She wants Burke to find a monster for her - so she can kill him with her bare hands. In this thriller, Andrew Vachss's renegade private eye teams up with a lethally gifted avenger to follow a child's murderer through the catacombs of New York, where every alley
Keywords: Burke (Fictitious character) -- Private investigators -- Mexican literature